Mangrove ecotourism - striking a balance between ecology and economics - Mohd. Yaman, Maheran; Ab Rahman, Nik Ismail Azlan (IIUM Press, 2009)
The development of mangroves as ecotourism sites is growing worldwide, at least within the subtropical regions of the world, which make up their habitat. One of the site is the Kukup Island which is the second largest species of mangrove forests in the world. The mangrove environments benefits from visitors because they help to conserve the environment; they in turn benefit from their non-consumptive use of the resource which economists refer to as use value as they increase their knowledge about the site visited; and this raises their utility level. The local community too should benefit from both the resource which has been sustaining their life and the visitors who bring them new sources of income. There is, therefore, a symbiotic relationship among the three involved in ecotourism. Mangrove tourism and for the "scholarly" type - those who want to learn the scientific aspects of the forest (flora and fauna), the economic and ecological benefits of mangroves to man, etc. Mangroves tourism also provides "educational recreation" by being physically involved in activities during the visit. A survey were conducted based on the individual travel cost method (ITCM) and their perception towards the mangrove environment. The findings suggest that a symbiosis relationship between the local community, visitors and mangrove ecotourism will help the stakeholders to plan and implement a better tourist management plan for the future.